2017
DOI: 10.1002/jbt.21965
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of proanthocyanidins against doxorubicin‐induced nephrotoxicity in rats

Abstract: Doxorubicin (DOX) exerts toxic effects in several organs particularly kidney. The present study aimed to assess the protective effect of proanthocyanidins (PAs) against DOX-induced nephrotoxicity in rats. A single dose of DOX (7.5 mg/kg, i.v.) significantly increased kidney weight, kidney/body weight ratio, serum urea, creatinine, tumor necrosis factor alpha levels, and kidney contents of malondialdehyde, nitric oxide, cyclooxygenase-2, and caspase-3 activity with significant reduction in final body weight, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 50 publications
4
19
0
Order By: Relevance
“…A huge number of studies demonstrated that oxidative stress has an important role in CsA‐induced nephrotoxicity . Also, as shown in many reports, antioxidant therapy appears to alleviate nephrotoxicity . In a previous study of ours, it was shown that CsA‐treated rats had higher serum soluble Klotho (a protein with antiaging and antioxidant properties) and oxidative stress markers than those in controls.…”
Section: Discussionsupporting
confidence: 66%
“…A huge number of studies demonstrated that oxidative stress has an important role in CsA‐induced nephrotoxicity . Also, as shown in many reports, antioxidant therapy appears to alleviate nephrotoxicity . In a previous study of ours, it was shown that CsA‐treated rats had higher serum soluble Klotho (a protein with antiaging and antioxidant properties) and oxidative stress markers than those in controls.…”
Section: Discussionsupporting
confidence: 66%
“…Alterations in the RAS have been shown to contribute to the development of AKI and are associated with adverse outcomes both in experimental and clinical studies [45][46][47][48][49][50]. Several components of the kidney RAS, such as urine Angiotensinogen and Ang II, the main active peptide, are increased in experimental AKI caused by ischemia-reperfusion AKI [45][46][47][51][52][53][54][55][56] ACE inhibitors (ACEi) and angiotensin receptor antagonists (ARBs) may attenuate renal inflammation, injury and improve renal function in the ischemia-reperfusion model of AKI [57][58][59][60]. Intrarenal Ang II is reportedly elevated in AKI, which may worsen kidney tissue injury independently of its hemodynamic effect that helps maintain renal circulation [61][62][63].…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact mechanism of DOX-induced hepatotoxicity and nephrotoxicity remains unknown, it is believed that the toxic effects are mediated by free radical formation, iron-dependent oxidative damage of biological macromolecules, membrane lipid peroxidation, and protein oxidation [15,19,24,25,26,66,67]. Moreover, nitric oxide synthase may be responsible for the reductive activation of DOX to its free radical semiquinone form, and the subsequent oxygen radical-mediated cellular damage.…”
Section: Discussionmentioning
confidence: 99%